Evaluation of students’ access to serial publications in three selected universities in ogun state, Nigeria (2018)
This study evaluates the extent to which serials publications are accessible and used for learning purposes by the students in Nigerian Universities. The descriptive survey research design was adopted with the study population made up of students from one federal government owned university, one selected state owned university and one selected private owned university in Ogun state. A self-constructed questionnaire was used for data collection in this study, was analyzed using descriptive statistics and Statistical Package for Social Scientists (SPSS). Findings revealed that Nigeria university students have access to different serial collections in academic libraries. Serial publications are available and students have equal access to serials publications in the library. Restriction of some serials materials to undergraduate constitutes impediments to the use of serials by students in the university libraries. Students who visit the library frequently to read Bulletins are better informed about the university issues. It was also revealed that students often visit the serial section in the Universities libraries for academic purposes. The Serial Librarian attitude affects student’s use of serial section. There is a need to create conducive environment for students and guide the student in the proper use of serial publications. Serial Librarians should be well guided to give the best to the students in the use of serial publications and there is need for various universities to subscribe to different online or electronic serials.